The Current Restructuring of Cuba's Sugar Agroindustry - José Alvarez (EDIS)
After remaining a leading world sugar producer for most of the twentieth century, Cuba's sugar agroindustry is currently undergoing a radical transformation. In spite of the interest that the process has generated outside of Cuba, very few details about its scope and impacts are known. The objective of this fact sheet is to partially fill that gap. This is EDIS document FE472, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published January 2004.